Strategi Pemberdayaan Petani Lahan Cetak Sawah Baru melalui LEISA: The Empowerment Strategy of Newly Irrigated Rice Field Farmers through LEISA - Eries Dyah Mustikarini; Ratna Santi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Many newly irrigated rice field farmers in Bangka district leave their land empty. Farmers choose to do other farming activities or mining activities rather than rice cultivation. The area of newly irrigated rice fields in Bangka district is currently 2,200 hectares. The development of newly irrigated rice fields aims to increase rice production. The research aims: (1) Knowing the strengths, weaknesses, opportunities, and threats faced by farmers in the cultivation of rice in Kimak village, (2) Alternative strategies for community empowerment to increase farmers' incomes. The research was conducted in July-November 2019. The community empowerment strategy applied in this research is the application of the LEISA concept. The research was conducted using observational methods, interviews, and experiments. The respondents involved were 30 farmers. The research results showed that the application of the LEISA concept generated a profit of Rp 1,974,722 per three months, in an area of 1,680m2. The implication, there is an increase in the number of farmers as many as 21 people who cultivate rice refers to the LEISA concept.